2015
DOI: 10.1111/pace.12696
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of Radiofrequency, Cryothermal, and Laser Left Atrial Lesion Formation in Patients with Atrial Fibrillation

Abstract: Background Catheter ablation utilizing radiofrequency (RF), Cryothermal (Cryo), or Laser energy is effective for treatment of atrial fibrillation (AF). Late gadolinium enhancement magnetic resonance imaging (LGE-MRI) has been used to estimate the burden of LA fibrosis, but no data exists regarding structural changes following each modality. We sought to compare the baseline to post-procedure change in left atrial (LA) scar burden following RF, Cryo, or Laser ablation for treatment of AF. Methods Seventeen pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…also reported that there was no difference in the PV antral LGE intensity between CB and RF ablation. However, the sample size was rather small (7 patients in the RF group and 5 in the CB group) . The LGE‐MRI acquisition protocol was consistent with other reports; however, the definition of the ablation lesion was still in debate.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…also reported that there was no difference in the PV antral LGE intensity between CB and RF ablation. However, the sample size was rather small (7 patients in the RF group and 5 in the CB group) . The LGE‐MRI acquisition protocol was consistent with other reports; however, the definition of the ablation lesion was still in debate.…”
Section: Discussionsupporting
confidence: 70%
“…Although the lesions after RF ablation have been reported to be visualized by LGE‐MRI in the previous studies, the difference in the LGE lesions between CB and RF ablation is still in debate . Malcome‐Lawes et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We sought to clarify the difference in the lesion characteristics after AF ablation using the two completely different balloon catheters and energy sources. On the basis of the lesion characterization assessed by LGE‐MRI, we would determine the optimal ablation strategy and improve the safety of the balloon catheter …”
Section: Introductionmentioning
confidence: 99%
“…In a study that was limited by the very small number of patients included, Khurram et al. compared the baseline to postprocedure change in LA scar burden following Laser (n = 5), RF (n = 5), and cryoablation (n = 7), using LGE‐CMR . In their study, late‐gadolinium enhancement showed no differences in scar area between cryoablation and Laser techniques, compared to RF ablation.…”
Section: Discussionmentioning
confidence: 99%